PERTUMBUHAN SETEK BEBERAPA VARIETAS Hoya coronaria DARI KAWASAN HUTAN KERANGAS AIR AINYIR, BANGKA - Ida Yulianti; Yulian Fakhrurrozi; Sri Rahayu (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2018)
The research on vegetative propagation of several H. coronaria varieties from heath forest of Air Anyir Bangka, is the first step to cultivate as well as for conservation purpuses. This research purpose to study the growth of stem cutting from several H. coronaria varieties as well as to find the best cutting method. This research was done on Oktober 2015 until January 2016 at trial house on Gabek 2, Pangkalpinang. The experiment applied randomized factorial completely design of 2 factors with 15 level combinations. The first factor is 5 variety of H. coronaria and the second factor is 3 cutting methods with different leaves numbers. Three replications was applied with 3 cutting each of replications. The parameters were observed on the establishment of cuttings (life cutting presentation), root length, root total number, shoot total number, shoot length, stem diameter, leaves total number, leaf wide and internode total number. The result showed that most of all growth parameters except stem diameter were significantly influenced by the varieties differences. All growth parameters were also significantly influenced by the cutting methods as well as all treatment interaction. This result was assumed influence by cutting age an 7 weeks. The best fast growth varieties was variety 5. The best cutting method was 4 leaves cutting. The best treatment interaction was variety 4 with 4 leaves cutting. The slowest growth varieties was variety 1, and the slowest cutting was non leaves cutting. This result were assumed influencing by some factors such us the numbers of leave, nutrition, hormone, genetic and environment.